The total station as a tool for recording provenance inpaleontology fieldwork: Configuration, use, advantages, and disadvantages - Bissaro, Marcos César; Ghilardi, Renato Pirani [UNESP]; Bueno, Matheus Rosario; Manzoli, Anderson; Adorni, Fernando Soares; Muniz, Fellipe Pereira; Guilherme, Edson; De Souza Filho, Jonas Pereira; Negri, Francisco Ricardo; Hsiou, Annie Schmaltz (Society for Sedimentary Geology, 2018)
Fossil data collecting is an essential stage of every paleontological undertaking. Although there is a consensus regarding the fundamental importance of sedimentary and stratigraphic context, there is still some debate surrounding the need to record the exact position of a fossil in relation to other elements within the same deposit (provenance). Here we provide a practical guide for the in-field use of the Total Station (TST, electronic equipment for xyz coordinates measurements), a tool that has seen wide application in archaeology but has been largely neglected in paleontology. With the TST, recording the provenance of in situ fossils can be done quickly and with great precision. We also present a configuration tutorial showing how to use the equipment, based on our experience in the Solimões Formation (upper Miocene, Acre basin, Brazil), highlighting both its advantages and disadvantages for recording fossil provenances.